Free verses by Emma Andiyevska of XXI century in the context of the evolution of the genre - Астапенко, Ігор Анатолійович (The Journal of V. N. Karazin Kharkiv National University. Series “Philology”, 2017)
The article researches the innovation of the verse libre structures by Emma Andievskoy of the new millennium, an experimental nature of her free verse in the context of the evolution of the genre is considered, the specifics of the creative thinking of the writer is clarified. Attempts of free diversification in the folk art, the origins of writing free verse in "Lay", free verse in the paradigm of Ukrainian baroque poetry, beginning of the Ukrainian classical vers libre in the works of Taras Shevchenko, Lesya Ukrainka, Ivan Franko and free verse experiments of the newest Epoch – Mykhailo Semenko, representatives of the New York poetry group, which Emma Andiyevska does not belong to are analyzed.